Bibliometric Analysis of Youtube Platform Research Trends Using the Vosviewer Application - Julia Yakir; Osthoff Valentin; Tamara Rosario (Yayasan Adra Karima Hubbi, 2023)
Background. Youtube is said to be a media called alternative media. This is said because YouTube makes it easy for teachers or students to be able to carry out learning very well and can make students have increased learning activities and material can be easily understood quickly. Purpose. The aim of this studyto find out the effect of using YouTube as an online learning material so that the teaching and learning process continues to run well). Method. The method used in this study is a bibliometric analysis technique that includes RIS data components indexed by journals and by discussing research on YouTube as a learning medium.. Results. This shows that YouTube learning media is well used as a learning medium. Conclusion. What can be taken is that YouTube learning media has a positive influence on ease of access, student interest in learning, and improving learning outcomes. In addition, research conducted using the keyword